O cinema de Júlio Bressane: transcriação e imagens da cultura - Sousa, Adriano Carvalho Araújo e (2010)
The analysis uses the concept of transcreation in Julio Bressane s films to consider the interaction between three languages: paintings, literature and music. The corpus consists of feature films from Brás Cubas (1985) to A Erva do Rato (2009). Turning to four of these films as a starting point and then stepping through the others, the purpose is to start by: paintings, from Filme de Amor (2003); literature, from Miramar (1997); and the music, since O Mandarim (1995) and Days of Nietzsche in Turin (2002). Transcreation (transcriação) was chosen as parsing support concept designed by Haroldo de Campos. And also proposing a certain debate with Henri Meschonnic to question the passage of these languages to cinema; and hold the debate over the essays about Julio Bressane s films. Instead of analyzing scene by scene or to bring a reference movie, as occurs in most of the bibliography about the filmmaker, I propose a collation sequences taken from a decoupage panel. The criterion of this division is not what paintings, literature and music means but what they build in order to the tone and rhythm of translations of signs to the cinema. There is thus an approach less alien to the bressanean poetic which founds a concept and interrogates what may prove to be a cinema of transcreation